Conflict Resolution Through Effective Communication - Bista, Binod Prasad (Tribhuvan University Journal, 2016)
Freedom of expression has surfaced in large parts of the world, particularly the newly independent nations and the countries that remained in isolation, along with the spread of democracies in those countries. With the rise of free expression of views often contesting with one another, conflicts of different kinds that were under suppression earlier, also emerged. Conflict in itself is considered neither good nor bad but it is judged by its outcome. Study of conflict, specifically the causes behind it relating to power struggle, economic competition, is important for achieving peace. One of the important tools for resolving conflicts is effective communication. Despite the stupendous advancement of information and communication technologies (ICTs), existence of digital divide has presented serious constraints in the application of available technologies. Potential of ICTs in conflict resolution is being increasingly recognized as it assists in promoting peace, preventing conflict through the use of early warning system. While the mobile technology generated SMS is credited for success of 'Arab Spring', considered as a non-violent method for regime change, there are also problems associated with it in fueling conflicts. It is, thus, necessary for communication, particularly media, to become transparent, reliable and ethical. Use of English language in doing business today cannot be overemphasized. Sometimes it requires more than language to resolve conflicts arising out of national interest related issues of the countries concerned. Sustainable peace demands intervention of a non-violent nature with consideration given to social justice and human rights. Effective communication in not merely an act of entering into dialogue and relaying views and perceptions to conflicting parties but also securing their trust and confidence in order to arrive at a mutually agreeable agreement for securing peace.